Suzuki-Miyaura coupling between 3-Iodolawsone and arylboronic acids. Synthesis of lapachol analogues with antineoplastic and antileishmanial activities - Gomes, Sara L. S. (2017)
A series of 2-hydroxy-3-arylnaphthalene-1,4-diones (3-aryllawsones) were synthesized by Suzuki-Miyaura cross coupling reaction of 3-iodolawsone with arylboronic acids/esters. The hydroxylated resulting products were transformed into their corresponding N , N -diethyl carbamates. The antineoplastic and antileishmanial activities of the compounds were evaluated and compared with lapachol and its carbamate, providing promising results.